2011
DOI: 10.1021/bm201165h
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Self-Assembly of Genetically Engineered Silk–Elastin-like Protein Polymers

Abstract: Silk-elastin-like protein polymers (SELPs), consisting of the repeating units of silk and elastin blocks, combine a set of outstanding physical and biological properties of silk and elastin. Due to the unique properties, SELPs have been widely fabricated into various materials for the applications in drug delivery and tissue engineering. However, little is known about the fundamental self-assembly characteristics of these remarkable polymers. Here we propose a two-step self-assembly process of SELPs in aqueous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
261
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 205 publications
(272 citation statements)
references
References 34 publications
11
261
0
Order By: Relevance
“…Other SELRs have been reported to form nano-objects with different shapes, ranging from nanoparticles to nanofibers, depending on the conditions and the SL to EL ratio 28,57,58 . Along with the reported evidence for other SELRs and their ability to spontaneously form fibers, and considering that the only difference between (EI)x2 and (EIS)x2 is the presence of SL blocks in the latter, it can be concluded that these blocks are responsible for the ability of these materials to eventually organize into fibrils under the conditions studied.…”
Section: Microscopic Observationmentioning
confidence: 99%
See 3 more Smart Citations
“…Other SELRs have been reported to form nano-objects with different shapes, ranging from nanoparticles to nanofibers, depending on the conditions and the SL to EL ratio 28,57,58 . Along with the reported evidence for other SELRs and their ability to spontaneously form fibers, and considering that the only difference between (EI)x2 and (EIS)x2 is the presence of SL blocks in the latter, it can be concluded that these blocks are responsible for the ability of these materials to eventually organize into fibrils under the conditions studied.…”
Section: Microscopic Observationmentioning
confidence: 99%
“…However, the stimuli-responsiveness of the EL block has not been exploited to any great extent to date and no complex molecular designs for that block showing advanced functionality have been reported. Furthermore, many SELR designs incorporate such a high SL percentage that the contribution of the elastomeric portion to the self-assembly process is imperceptible 27,28 . However, experience with SELR designs with a lower SL content has demonstrated that, in such compositions, the EL blocks are able to maintain their characteristic thermal transition [28][29][30] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such properties are maintained when GAGAGS motifs are engineering along an ELR molecule, giving rise to so-called SELR (silk-elastin like recombinamer). Many SELR-based hydrogels have been reported in the literature [94][95][96][97] and some of them have been successfully explored for drug-delivery purposes. [98][99][100][101] Indeed, the utility of SELRs has been explored in both the field of drug delivery and for the delivery of viral vectors.…”
mentioning
confidence: 99%